Cooperatives : (kilusang bayan) - Fajardo, Feliciano R.; Abella, Fabian P. (Manila, Philippines : Rex Book Store, 1981)
This book is not written only to provide general information on cooperatives for the benefit of students and other readers. Over and above the traditional treatment of the course, it is designed to infuse into the character of our college students the proper values and knowledge which they should assimilate to improve their social orientation and community leadership.
Chapter 1. History of cooperation -- 2. Principles and practices of cooperatives -- 3. Organization and management of cooperatives -- 4. Philippines - cooperative development program -- 5. Samahang nayon -- 6. Credit cooperative -- 7. Consumers cooperatives -- 8. Service cooperatives -- 9. Producers and marketing cooperatives -- 10. Cooperatives in selected countries: an overview -- 11. Cooperatives and the agrarian reform program -- 12. Cooperatives and the major economic systems -- 13. The role of cooperatives in community development -- 14. Development of people through cooperatives -- 15. Problems and prospects -- Bibliography.
Includes bibliographical references.
Keywords: COOPERATIVES